Volatility to sustainability: Examining the implications of a play-to-earn game in the Metaverse - Camelo, Jay Lawrence T. (Animo Repository, 2022)
The paper explores the impacts of play-to-earn games, particularly Axie Infinity, on an individual’s well-being, as well as to gather insights about the quality of Axie Infinity’s play-to-earn business model, and if the implementation of a play-to-earn system is economically feasible. The researchers, through a single embedded case study coupled with a descriptive approach using Systems Thinking and the Stakeholder Theory, conducted interviews with three (3) groups, each consisting of one (1) manager and two (2) scholars, all based in Metro Manila, Philippines. Through this, it was found that Axie Infinity was able to satisfy the physiological needs of its players, most notably moral development, social development, emotional development, and cognitive development as it gave the stakeholders the chance to learn, earn, enjoy, and support them financially. Additionally, Axie Infinity’s play-to-earn mechanic becomes similar to a Ponzi scheme since the growth is dependent on the number of new players and since the game needs more $SLP functionality aside from the already available breeding. Apart from the lack of academic literature concerning Axie Infinity and play-to-earn games, this research is valuable due to the considering the viability of Axie Infinity as another avenue for Filipinos to earn and analyze the upcoming metaverse trend to determine the limitations and improvements that can be made to better sustain life in this new system.